PEMBUATAN GAME 3D CORONA SURVIVAL MENGGUNAKAN UNITY BERBASIS ANDROID - Jeswit Pulohot Haromunthe; Joko Riyanto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Games can be used as a means of education that is happening in the surrounding environment, suchas the Covid-19 pandemic that has hit the whole world. The media for information circulating on Covid-19 is still minimal for children. The dangers of Covid-19 and invitations for vaccines can be conveyed through childfriendly media in the form of games. Games also have other benefits such as brain development, practice solving problems, increasing concentration, training speed and others. Currently, the games in circulation are still used for entertainment and can be addictive. Corona Survival game is an example of a child-friendly educational game media. This game is made using the Game Development Life Cycle method. Many people do not know about educational games, due to the lack of educational games compared to other games.